Comparison Study of Malaysian Driver Seating Position in SAEJ1517 Accommodation Model - Rashid, Zuli'zam; Bakar, Nooh Abu; Dolah, Rozzeta; Ghazilla, Raja Ariffin Raja (SAE International, 2019)
A key element in an ergonomically designed driver’s seat in a car is the correct identification of driver seating position and posture accommodation. Current practice by the automotive Original Equipment Manufacturer (OEM) is to utilize the Society of Automotive Engineering (SAE) J1517 standard practice as a reference. However, it was found that utilizing such guidelines, which were developed based on the American population, did not fit well with the anthropometry and stature of the Malaysian population. This research seeks to address this issue by comparing the SAE J1517 Model against Malaysian preferred driving position. A total of 62 respondents were involved for the driver seating position and accommodation study in the vehicle driver’s seat buck mockup survey and measurements. The results have shown that the Malaysian drivers prefer to sit forward as compared to the SAE J1517 Model and have shorter posture joint angle. This could significantly affect the design of the driver seat positions and layout of other driving elements, suggesting a need to reconsider its application, in particular for the Malaysian population. Copyright © 2019 SAE International.